UMPSA students excel at 3rd International Summer School on Sustainability - Logathepan, Muniyappan; Ahmad Fauzan, Ahmad Faizul; Kong, Zhen Mike; Myra Anne, Miranda (UMPSA, 2024)
Karlsruhe, Germany, 9 September 2024 – Four exemplary students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) were selected to participate in the 3rd International Summer School on Sustainability, hosted by Karlsruhe University of Applied Sciences (HKA) from 9 to 13 September 2024.